Improving Coffee Processing Towards Community-Based Agritourism - I Gede Pasek Mangku; I Made Astu Mahayana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The quality and flavor of coffee products are influenced by the processing used. Suitable processing methods can increase coffee products' quality, flavor, and bioactive content. Better coffee quality can support the agritourism development program in the Harapan Maju group. This community service aims to improve the knowledge and skills of Harapan Maju group on processing coffee and to increase communication skills in English to sell and promote their products. The methods used in this program are surveys, observation, transfer of knowledge and skill, mentoring, documentation, as well as practicing. There are 28 participants from the group who joined in this activity. The result showed that the knowledge and skill of the group members are increasing therefore, the Harapan Maju group can produce coffee products with good quality and flavor to support agritourism programs. Otherwise, the ability of English communication skills also increases and can support agritourism development in the future. However, the group continuously needs mentoring and guidance from the University and government.